2005
DOI: 10.1097/01.bpo.0000152906.23669.d8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temporary Hemiepiphyseal Stapling on the Growth Plate

Abstract: The purpose of this study was to investigate the effect of temporary hemiepiphyseal stapling on the bone geometry and proliferative activity of the physis in immature rabbits. Proximal medial epiphyseal stapling of the right tibia was performed in 46 6-week-old New Zealand white rabbits. The rabbits were assigned randomly into two groups. In group 1, the staples were inserted extraperiosteally and the rabbits were killed at the end of 3 weeks. In group 2, the staples were fixed subperiosteally (group IIA) or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
(32 reference statements)
0
34
0
2
Order By: Relevance
“…staples or percutaneous screws (PETS) is awaiting further study [27]. We have undertaken research in New Zealand rabbits to elucidate the response of the physis to flexible vs .…”
Section: Discussionmentioning
confidence: 99%
“…staples or percutaneous screws (PETS) is awaiting further study [27]. We have undertaken research in New Zealand rabbits to elucidate the response of the physis to flexible vs .…”
Section: Discussionmentioning
confidence: 99%
“…He proposed the use of three staples, suggesting that this was the ideal construct to maximize the correction while minimizing the risk of hardware failure. Blount also observed that, after removing the staples, the physis recovered its ability for continued growth [3, 8, 9]. This is in contrast to methods typically performed near the end of growth which cause complete, irreversible growth arrest [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The technique requires an open approach, and care should be taken to avoid damaging the periosteum, the perichondrial ring, and epiphyseal vessels. The latter may result in iatrogenic permanent physeal arrest or, in contrast, rebound overgrowth [17][18][19]. When hemiepiphyseal stapling was compared with PETS for the correction of angular deformities, no significant difference was observed in the mean rate of angular correction, the physeal behavior after implant removal, or the number of complications [12].…”
Section: Discussionmentioning
confidence: 77%